Preparation and Characterization of PEI/SPES Composite Nanofiltration Membrane - TAN, LINGYAN; ZHANG, HAOQIN; LIU, JINDUN (Asian Journal of Chemistry, 2010)
A novel composite nanofiltration membrane carrying two kinds of charge was fabricated by coating negatively charged sulfonated polyethersulfone (SPES) microporous membrane with positively charged polyethyleneimine (PEI). Effects of membrane forming and operating conditions on PEI/SPES membrane properties are measured. The separation efficiency was tested by separating salt from dye mixtures. In addition, the morphology was characterized through scanning electron microscopy and atomic force microscopy. The experimental results show that PEI/SPES membranes have high salt permeability whereas retaining PEG1000. Meanwhile, the properties of PEI/SPES membranes were influenced to a great extent by operation pressure and salt concentration. For dye mixture solutions, the separation factors were all more than 8.0, indicating that PEI/SPES membrane can be used for purification of dyes. Since PEI/SPES membrane carries two kinds of charge to facilitate salts transition, this property makes it a promising candidate for the desalination of water-soluble organics mixture system.